The value of structural brain imaging in explaining individual differences in children's arithmetic fluency. (November 2021) - Polspoel, Brecht; Vandermosten, Maaike; De Smedt, Bert
Abstract: How do different measures of brain structure correlate with individual differences in arithmetic fluency? This paper builds on two previously published studies in which individual differences in children's arithmetic fluency were correlated with measures of white (Polspoel et al., 2019 ) and grey matter (Polspoel et al., 2020 ) in one sample of children. We combined the brain imaging data of these two studies with measures of cognitive abilities that have been shown to be predictive of arithmetic fluency, i.e., numerical magnitude processing, working memory and rapid automatized naming (RAN). This allowed us to investigate to which extend the observed structural brain imaging measures uniquely correlated with children's arithmetic fluency, on top of each other as well as on top of the abovementioned cognitive variables. Participants were 43 typically developing 9-10-year-olds. All measures were added to a hierarchical multiple regression model. This regression model showed that the white matter integrity of the right inferior longitudinal fasciculus and the cortical complexity of the left postcentral gyrus remained unique predictors of individual differences in arithmetic when the abovementioned cognitive variables were taken into account. This indicates that structural neuroimaging measures can explain individual differences in arithmetic performance that are not merely accounted for by relevant cognitive predictors.